Carbon nanotube embedded artificial cell, preparation method thereof and application of carbon nanotube embedded artificial cell in degradation of antibiotic resistance genes
By constructing carbon nanotube-embedded artificial cell materials, the problems of metal ion leaching and difficulty in recycling during the activation of persulfate degradation of antibiotic resistance genes by cobalt-based catalysts were solved, achieving a green degradation effect with efficient catalysis and convenient recycling.
Patent Information
- Application Number
- CN202511667315.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-14
- Publication Date
- 2026-01-16
AI Technical Summary
Existing cobalt-based catalysts have problems such as high risk of metal ion leaching, insufficient cobalt ion recycling efficiency, and easy agglomeration and deactivation of nanomaterials when activated by persulfate degradation of antibiotic resistance genes, making them difficult to recycle and reuse.
By calcining CoFe-LDH with carbon spheres, layered double oxide hollow spheres were derived. Liposome encapsulation technology was used to construct artificial cells with confined spatial structures, and carbon nanotubes were embedded in the cell membrane as material transport channels to form carbon nanotube embedded artificial cell materials.
It effectively inhibits the leaching of metal ions, improves the activation efficiency of persulfate, promotes the transport of reactants and products, achieves efficient and green degradation of antibiotic resistance genes, and facilitates material recycling through magnetic design.
Smart Images

Figure CN121338840A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental functional materials and biological pollution control technology, specifically relating to a carbon nanotube embedded artificial cell material for the efficient degradation of antibiotic resistance genes (ARGs) in water, its preparation method, and its application in advanced oxidation processes (AOPs). Background Technology
[0003] Currently, the main technologies for controlling ARGs in the environment include adsorption, biodegradation, and membrane separation processes. However, these traditional methods generally suffer from limited degradation efficiency, high operating costs, or the potential for secondary pollution. Especially when dealing with low concentrations and high stability of extracellular ARGs, conventional processes often fail to achieve effective removal. Advanced oxidation processes (AOPs) have attracted widespread attention because they can completely degrade organic pollutants by generating highly reactive oxygen species (ROS). Among them, persulfate (PMS)-based AOPs technology shows unique advantages due to its ability to generate various highly reactive oxygen species such as sulfate radicals and hydroxyl radicals. However, PMS itself is not effective in degrading ARGs and requires catalyst activation to generate sufficient ROS.
[0004] Cobalt-based catalysts exhibit excellent catalytic performance in PMS activation; however, the pure cobalt / PMS system suffers from low cobalt ion cycling efficiency and high metal ion dissolution rate, which not only affects catalytic efficiency but may also cause secondary water pollution. Iron-based co-catalysts have been introduced into cobalt-based catalytic systems due to their environmental friendliness and low cost. Fe(II) can promote the redox cycle of high-valence metals and enhance the generation of active species. Cobalt-iron layered bimetallic hydroxides (CoFe-LDH) show application potential in catalysis, adsorption, and electrochemistry due to their unique layered structure, tunable metal ratio, and good catalytic activity. However, directly adding nanomaterials such as CoFe-LDH to water still faces challenges such as metal ion leaching, material agglomeration and deactivation, and difficulty in recycling and reuse.
[0005] To address the aforementioned issues, there is an urgent need to develop novel catalytic materials that maintain high catalytic performance while minimizing metal ion leaching and facilitating recycling. Based on this, we derived layered double oxide hollow spheres (LDO-HSs) by calcining CoFe-LDH with carbon spheres. Then, we constructed artificial cells with confined spatial structures using liposome encapsulation technology and embedded carbon nanotubes within the cell membrane as material transport channels, ultimately developing this carbon nanotube-embedded artificial cell material. This design retains the high catalytic performance of CoFe-LDH in activating PMS to generate ROS, while effectively inhibiting metal ion leaching through the physical barrier effect of the artificial cells. Simultaneously, the carbon nanotube channels promote efficient transport of reaction substrates and products, providing a new technical approach for the efficient and green degradation of ARGs. Summary of the Invention
[0006] Technical problems solved: In view of the problems of high risk of metal ion leaching, insufficient cobalt ion recycling efficiency, and easy agglomeration and deactivation of nanomaterials when directly added to cobalt-based catalysts for activating persulfate to degrade antibiotic resistance genes, the present invention provides a carbon nanotube embedded artificial cell material, its preparation method and application. This invention aims to achieve the following technical objectives through material structure innovation and functional integration: First, it constructs an artificial cell with a confined spatial structure to encapsulate catalytically active components, effectively isolating the complex components of water from interfering with the catalytic center, while significantly inhibiting the leaching of metal ions into the water and avoiding secondary pollution; Second, it utilizes the directional transport channels formed by embedding carbon nanotubes into the artificial cell membrane to promote efficient mass transfer between persulfate molecules and reactive oxygen free radicals, and accelerates the redox cycle of the cobalt / iron bimetallic active center through its unique electronic conduction properties, thereby improving the activation efficiency and reaction kinetics of persulfate; Finally, through the intrinsic magnetism of cobalt-iron layered double hydroxide and its hollow spherical structure design, the material is endowed with the characteristic of easy magnetic separation and recovery, achieving efficient degradation of antibiotic resistance genes while overcoming the shortcomings of traditional homogeneous and heterogeneous catalytic systems in terms of stability, safety, and sustainability.
[0007] Technical Solution: A method for preparing carbon nanotube embedded artificial cell material, comprising the following steps: (a) preparing carbon spheres: using D-glucose and boric acid as raw materials, wherein the mass ratio of D-glucose to boric acid is (7-9):1, carbon spheres are obtained through hydrothermal reaction, centrifugation, washing, and drying; (b) preparing cobalt-iron layered double hydroxide: by co-precipitation, a mixed nitrate solution of cobalt salt and iron salt is mixed with an alkaline solution, wherein the molar ratio of cobalt ions to iron ions is (1-5):1, and the total metal ion concentration is 0.3-0.6%. (c) Preparation of layered double oxide hollow spheres: The carbon spheres obtained in step (a) and the cobalt-iron layered double oxide obtained in step (b) are ultrasonically dispersed in water, centrifuged, dried, and then calcined to obtain layered double oxide hollow spheres; the mass ratio of the cobalt-iron layered double oxide to the carbon spheres is (7-3):2; (d) Construction of artificial cells and embedding of carbon nanotubes: Liposome films are formed by thin film hydration, and buffer solution is added for hydration to obtain artificial cell base solution; the layered double oxide hollow spheres obtained in step (c) are hydrated with liposome films to obtain artificial cells encapsulated with layered double oxide hollow spheres; finally, the purified carbon nanotubes and artificial cell solution are mixed at a volume ratio of 1:(1-3), mechanically shaken and incubated in a water bath to obtain the carbon nanotube embedded artificial cell material.
[0008] In step (a), the mass ratio of D-glucose to boric acid is 8:1; the hydrothermal reaction temperature is 180°C; and the reaction time is 6 hours.
[0009] In step (b), the molar ratio of cobalt ions to iron ions in the mixed nitrate solution is 2:1, and the total metal ion concentration is 0.5 mol / L; the alkaline solution is a mixed solution of sodium hydroxide and sodium carbonate with a molar ratio of 1:1, and the pH value of the reaction system is maintained at 10.
[0010] In step (c), the mass ratio of the cobalt-iron layered double hydroxide to the carbon spheres is 5:2; the calcination temperature is 500℃ and the calcination time is 8 hours.
[0011] In step (d), the liposomes are 2-oleoyl lecithin; the buffer solution is PBS solution; and the volume ratio of the carbon nanotubes to the artificial cell solution is 1:2.
[0012] The carbon nanotube embedded artificial cell material prepared by the above method.
[0013] In the aforementioned carbon nanotube embedded artificial cell material, the layered double oxide hollow spheres are cobalt-iron layered double oxide hollow spheres.
[0014] The application of the aforementioned carbon nanotube-embedded artificial cell material in the catalytic degradation of antibiotic resistance genes.
[0015] The above-mentioned catalytic degradation process includes: mixing the carbon nanotube-embedded artificial cell material with a solution containing antibiotic resistance genes for adsorption reaction, and then adding persulfate solution to initiate the catalytic degradation reaction.
[0016] The concentration of the carbon nanotube-embedded artificial cell material in the reaction system was 200 mg / L; the concentration of the persulfate in the reaction system was 300 mg / L; and the adsorption reaction time was 30 minutes.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0018] This invention encapsulates a cobalt-iron layered double hydroxide within an artificial cell and utilizes embedded carbon nanotubes to construct transport channels. This effectively blocks interference from complex water components on the catalytic active centers, significantly inhibiting the leaching of cobalt, iron, and other metal ions, and overcoming the secondary pollution problems that may arise from traditional heterogeneous catalytic systems. Carbon nanotubes not only act as efficient electron conduction channels, accelerating electron migration between the cobalt / iron bimetals and promoting the activation efficiency of persulfate, but also enrich the reaction substrate through their unique surface properties, enhancing the interfacial reaction process. The synergistic effect of the cobalt-iron bimetallic active centers enables the material to preferentially generate highly selective singlet oxygen and superoxide radicals during persulfate activation. These reactive oxygen species can directly attack the phosphodiester bonds and base structures of resistance genes, achieving efficient gene fragmentation and inactivation. The layered double oxide hollow sphere structure formed inside the material not only provides abundant catalytic active sites, but its inherent magnetic properties also enable rapid separation and recycling under an external magnetic field. Experiments show that the material retains a high magnetic response capability after the catalytic reaction. This design concept, which integrates efficient catalysis, confined protection, and convenient recycling, provides a technical solution with practical application potential for the green and sustainable management of antibiotic resistance genes in the environment. Attached Figure Description
[0019] Figure 1 Transmission electron microscopy (TEM) images of (a) CSs, (b) CoFe-LDH, (c) CSs@LDHs, and (d) LDO-HSs.
[0020] Figure 2 X-ray diffraction images of (a) CSs, (b) CoFe-LDH, (c) CSs@LDHs, and (d) LDO-HSs.
[0021] Figure 3Infrared images of (a) CSs, (b) CoFe-LDH, (c) CSs@LDHs, and (d) LDO-HSs.
[0022] Figure 4 The images are (a) transmission electron microscopy (TEM) images of artificial cells, (b) TEM images of diced carbon nanotubes, (c) TEM images of artificial cells encapsulated with liposomes, and (d) TEM images of LDO-HSs@ArtifCell@CNTs.
[0023] Figure 5 (a) XPS full spectrum of LDO-HSs before and after catalytic reaction, (b) Fe 2p fitting results of LDO-HSs before and after catalytic reaction, and (c) Co 2p fitting results of LDO-HSs before and after catalytic reaction.
[0024] Figure 6 (a) Standard curve of QPCR pBR322 at the manufacturer's reported concentration, (b) Degradation characteristics of different materials.
[0025] Figure 7 The hysteresis loops are those of CSs@LDHs, LDO-HSs, and LDO-HSs after catalytic reaction at room temperature.
[0026] Figure 8 For (a) DMPO-•OH / SO4 in the presence of LDO-HSs - Electron paramagnetic resonance spectra measured in aqueous solution, (b) DMPO- in the presence of LDO-HSs. 1 Electron paramagnetic resonance spectra measured in O2 aqueous solution, (c) DMPO-·O2 in the presence of LDO-HSs. - Electron paramagnetic resonance measured in aqueous solution. Detailed Implementation
[0027] Example 1: Preparation of carbon nanotube embedded artificial cell material
[0028] (1) Preparation of CSs: Weigh 8 g of D-glucose and 1 g of boric acid, dissolve them in 40 mL of deionized water, and then transfer the solution to a flask for a hydrothermal reaction for 60 min. After the reaction, pour the solution into a high-temperature reactor, place it in an oven, and incubate it at 180 °C for 6 h. Centrifuge the product after the reaction, wash it with deionized water, and filter it, repeating the process three times. Finally, place the collected product in an oven, dry it overnight at 60 °C, and then collect and store it.
[0029] CoFe-LDH was synthesized via a coprecipitation method. A mixed nitrate containing 16.667 mmol Co(NO3)2·6H2O and 8.333 mmol Fe(NO3)3·9H2O (Co:Fe = 2:1) (total metal ion concentration 0.5 mol / L) was dissolved in 50 mL of deionized water. Then, 50 mL of an alkaline solution consisting of 1 mol / L NaOH and 1 mol / L Na2CO3 was added dropwise to the metal salt solution, maintaining the pH at 10. The resulting suspension was then continuously stirred in a water bath at 65 °C for 20 h. Finally, the precipitate was centrifuged, washed with deionized water, and dried and ground after the supernatant reached neutral pH. The resulting product was named CoFe-LDH.
[0030] To prepare CSs@LDHs, 0.1 g of CoFe-LDH and 0.04 g of CSs were added to 20 mL of pure water and dispersed by ultrasonication for 1 h to uniformly disperse CoFe-LDH on the CSs surface. The mixture was then centrifuged at 8000 rpm for 5 minutes, and the CSs@LDHs were obtained by centrifugation once. The prepared material was placed in a forced-air drying oven and dried overnight at 60 °C.
[0031] To prepare LDO-HSs, CSs@LDHs powder was placed in a crucible and then calcined in a muffle furnace at 500 °C for 8 hours (5 °C / min) to obtain the final product LDO-HSs.
[0032] The materials prepared in this embodiment were characterized by transmission electron microscopy, X-ray diffraction, and Fourier transform infrared spectroscopy. The results are as follows: Figure 1 , Figure 2 and Figure 3 As shown. Figure 1 (a) Transmission electron microscopy (TEM) image of CSs, (b) Transmission electron microscopy image of CoFe-LDH, (c) Transmission electron microscopy image of CSs@LDHs, (d) Transmission electron microscopy image of LDO-HSs. Figure 2 (a) X-ray diffraction image of CSs, (b) X-ray diffraction image of CoFe-LDH, (c) X-ray diffraction image of CSs@LDHs, (d) X-ray diffraction image of LDO-HSs. Figure 3 Infrared images of (a) CSs, (b) CoFe-LDH, (c) CSs@LDHs, and (d) LDO-HSs. (The images are presented in the original text.) Figure 1 , Figure 2 and Figure 3 It can be seen that CSs, CoFe-LDH, CSs@LDHs and LDO-HSs were successfully prepared.
[0033] (2) Preparation of LDO-HSs@ArtifCell: 10 mg of 2-oleoyl lecithin was weighed and dissolved in 2 mL of chloroform solution, and incubated in a 37 ℃ water bath for 20 minutes. Then, the solution was poured into a single-necked round-bottom flask, mounted on the sample rack of a rotary evaporator, the heating switch was turned on, the temperature was adjusted to 45 ℃, and then the vacuum pump and rotary evaporator were turned on for reduced pressure evaporation. After the liquid in the single-necked round-bottom flask had evaporated and formed a film, it was removed. The obtained film was dried in a vacuum drying oven for 4 hours, and then vortexed with 2.5 mL of PBS solution at 25 ℃ for 5 minutes to obtain an emulsion suspension, i.e., artificial cells. Finally, the obtained suspension was passed through a 500 nm polycarbonate membrane twice using a liposome extruder to obtain an artificial cell solution of the ideal size, which was stored in a 4 ℃ refrigerator. Weigh 4 mg of LDO-HSs and add them to a flask with a liposome membrane at the bottom. Then add 2 mL of PBS solution to dissolve them and vortex hydrate at 25 °C for 5 minutes to obtain LDO-HSs@ArtifCell. Store it in a refrigerator at 4 °C.
[0034] Add 1 mL of purified CNTs and 2 mL of the prepared LDO-HSs@ArtifCell solution to a 5 mL centrifuge tube. Shake mechanically for 10 minutes, then incubate at 37 °C for 30 minutes to allow effective interaction between the components. The final solution is LDO-HSs@ArtifCell@CNTs, which should be stored at 4 °C until needed.
[0035] The material prepared in this embodiment was characterized by transmission electron microscopy, and the results are as follows: Figure 4 As shown. Figure 4 (a) Transmission electron microscopy (TEM) image of an artificial cell; (b) TEM image of a cleaved carbon nanotube; (c) TEM image of an artificial cell encapsulated with liposomes; (d) TEM image of LDO-HSs@ArtifCell@CNTs. (Images from the image are provided.) Figure 4 It is known that artificial cells, carbon nanotubes, artificial cells encapsulated with liposomes, and LDO-HSs@ArtifCell@CNTs have been successfully prepared.
[0036] Example 2: Catalytic Degradation of ARGs Test
[0037] First, add 20 mL of a certain concentration (10) 12ARGs solution (copies / mL) was added to a 50 mL beaker, followed by the synthesized LDO-HSs@ArtifCell@CNTs material, forming a solution with a material concentration of 200 mg / L. The adsorption reaction was carried out under mechanical stirring for 30 min. ARGs solutions from 0 min and 30 min of adsorption were filtered through a 0.22 μm aqueous membrane and added to a solution containing 10 μL of 20 g / L sodium thiosulfate quencher. After the adsorption reaction was complete, a catalytic degradation experiment was performed. 100 μL of PMS solution (final oxidant concentration 300 mg / L) was added to a beaker, and ARGs solutions from different time points were filtered through a membrane and added to the solution containing the quencher.
[0038] Then, the concentration of ARGs in the solutions taken at different time points was detected by PCR. 10 μL of HPOGreen qPCR Master Mix, 0.8 μL of 10 μM forward primer, 0.8 μL of 10 μM reverse primer, 5 μL of DNA template (i.e., the ARGs solutions taken at different time points), and 3.4 μL of ddH2O were added to each well of a 96-well plate, with three replicates for each time point. Finally, the mixed system was vortexed, centrifuged, and then placed in a PCR instrument for detection under the following cycling conditions: pre-denaturation at 95 ℃ for 1 min (1 cycle), denaturation at 95 ℃ for 1 sec (40 cycles), and annealing extension (fluorescence collection) at 60 ℃ for 30 sec (40 cycles). After the detection, the degradation effect was analyzed. We optimized the influencing factors of the catalytic reaction using a controlled variable method and conducted a series of characterization studies to explore the degradation pathway and performance of the material.
[0039] X-ray photoelectron spectroscopy was performed on the hollow spherical hydrotalcite material of this embodiment, and the results are as follows: Figure 5 As shown, Figure 5 XPS spectra of LDO-HSs before and after the catalytic reaction. (a) Full XPS spectra of LDO-HSs before and after the catalytic reaction; (b) Fe 2p fitting results of LDO-HSs before and after the catalytic reaction; (c) Co 2p fitting results of LDO-HSs before and after the catalytic reaction. Figure 5 The results show that hollow spherical hydrotalcite material was successfully synthesized, and the material structure was not destroyed after the catalytic reaction.
[0040] Example 3: Catalytic Degradation Performance Analysis
[0041] To better evaluate the ability of different materials to activate PMS to degrade ARGs under the same reaction conditions ([catalyst] = 200 mg / L, [PMS] = 300 mg / L, temperature = 25 ℃, [ARG] = 10), 12 Six plasmid standard solutions of different concentrations (copies / mL, reaction time = 30 min) were selected and a standard curve was plotted for subsequent experimental data processing.
[0042] Six concentrations of plasmid standard solutions, such as Figure 6 As shown. (a) Standard curve of qPCR pBR322 at the manufacturer's reported concentration, covering 10 6 - 10 12 (b) Degradation characteristics of different materials, with copies / mL ranging from six orders of magnitude. Figure 6 The results showed that the concentration of ARGs remained almost unchanged in the first 30 min, the adsorption removal was negligible, and that PMS was highly sensitive to the activation of LDO-HSs@ArtifCell@CNTs as an oxidant, showing great potential for drug degradation.
[0043] Example 4: Material Recycling
[0044] The differences in magnetic properties of the CSs@LDHs precursor, calcined LDO-HSs, and LDO-HSs after catalytic reaction were analyzed using a vibrating sample magnetometer (VSM) system. The results are as follows: Figure 7 As shown, Figure 7 The hysteresis loops are those of CSs@LDHs, LDO-HSs, and LDO-HSs after catalytic reaction at room temperature. Figure 7 The results show that CSs@LDHs exhibits weak magnetism, while the LDO-HSs formed after calcination possesses strong magnetism, with a saturation magnetization reaching 16 emu / g. After the catalytic reaction, the magnetic properties of the material decrease slightly compared to before the reaction, possibly due to the oxidation of some LDOs into LDHs. The high magnetic properties of LDO-HSs not only improve the ease of recovery but also enhance the electron migration capability of its internal ferrites, promoting PMS activation. This provides a theoretical basis for designing integrated materials that combine high-efficiency catalysis with convenient recovery.
[0045] Example 5: Catalytic Mechanism Analysis
[0046] Its response mechanism in PMS-induced AOP was further evaluated, and the results are as follows: Figure 8 As shown, Figure 8 The electron paramagnetic resonance spectra of the active free radicals generated in the catalytic reaction system are shown in (a) DMPO-•OH / SO4 in the presence of LDO-HSs. -Electron paramagnetic resonance spectra measured in aqueous solution, (b) DMPO- in the presence of LDO-HSs. 1 Electron paramagnetic resonance spectra measured in O2 aqueous solution, (c) DMPO-·O2 in the presence of LDO-HSs. - Electron paramagnetic resonance measured in aqueous solution. Figure 8 The results showed that no •OH / SO4 was generated in the LDO-HSs / PMS system. - ,have 1 The generation of O2 and the electron transfer process in the catalytic reaction.
Claims
1. A method for producing a carbon nanotube-embedded artificial cell material, characterized by, The method comprises the following steps: (a) preparing carbon spheres: taking D-glucose and boric acid as raw materials, the mass ratio of D-glucose to boric acid being (7-9): 1, and obtaining carbon spheres through hydrothermal reaction, centrifugation, washing and drying; (b) preparing cobalt-iron layered double hydroxide: mixing a mixed nitrate solution of cobalt salt and iron salt with an alkaline solution through coprecipitation, the molar ratio of cobalt ions to iron ions being (1-5): 1, and the total metal ion concentration being 0.3-0.6 mol / L, and obtaining cobalt-iron layered double hydroxide through water bath stirring, centrifugation, washing and drying; (c) preparing layered double hydroxide hollow spheres: ultrasonic dispersing the carbon spheres obtained in step (a) and the cobalt-iron layered double hydroxide obtained in step (b) in water, centrifuging, drying, and then calcining to obtain layered double hydroxide hollow spheres; the mass ratio of the cobalt-iron layered double hydroxide to the carbon spheres being (7-3): 2; (d) constructing artificial cells and embedding carbon nanotubes: forming a liposome film by adopting a thin film hydration method, adding a buffer solution to hydrate to obtain an artificial cell base solution; hydrating the layered double hydroxide hollow spheres obtained in step (c) and the liposome film to obtain artificial cells encapsulating the layered double hydroxide hollow spheres; and finally mixing purified carbon nanotubes with the artificial cell solution at a volume ratio of 1: (1-3), mechanically shaking and water bath incubating to obtain the carbon nanotube embedded artificial cell material.
2. The production method according to claim 1, characterized by, In step (a), the mass ratio of D-glucose to boric acid is 8:1, the hydrothermal reaction temperature is 180℃, and the reaction time is 6 hours.
3. The preparation method according to claim 1, characterized in that, In step (b), the molar ratio of cobalt ions to iron ions in the mixed nitrate solution is 2:1, the total metal ion concentration is 0.5 mol / L, the molar ratio of the mixed solution of sodium hydroxide and sodium carbonate in the alkaline solution is 1:1, and the pH value of the reaction system is maintained at 10.
4. The preparation method according to claim 1, characterized in that, In step (c), the mass ratio of the cobalt-iron layered double hydroxide to the carbon spheres is 5:2, the calcination temperature is 500℃, and the calcination time is 8 hours.
5. The preparation method according to claim 1, characterized in that, In step (d), the liposome is 2-oleoyl lecithin, the buffer solution is a PBS solution, and the volume ratio of the carbon nanotube to the artificial cell solution is 1:
2.
6. The carbon nanotube embedded artificial cell material prepared by the method of any one of claims 1 to 5.
7. The carbon nanotube-embedded artificial cell material of claim 6, wherein, The layered double hydroxide hollow spheres are cobalt-iron layered double hydroxide hollow spheres.
8. The use of the carbon nanotube embedded artificial cell material of claim 6 in catalytic degradation of antibiotic resistance genes.
9. Use according to claim 8, characterized in that, The catalytic degradation process comprises: mixing the carbon nanotube embedded artificial cell material with a solution containing antibiotic resistance genes to perform an adsorption reaction, and then adding a persulfate solution to start a catalytic degradation reaction.
10. Use according to claim 9, characterized in that, The concentration of the carbon nanotube embedded artificial cell material in the reaction system is 200 mg / L, the concentration of the persulfate in the reaction system is 300 mg / L, and the adsorption reaction time is 30 minutes.